PEMETAAN KERENTANAN DAERAH POTENSI LIKUIFAKSI, AKIBAT GEMPABUMI TEKTONIK STUDI KASUS DAERAH DESA PANJANGREJO DAN SEKITARNYA, KECAMATAN PUNDONG, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Alwyn Taufana Jati Putra (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Earthquake, is an event that generally occurs in the places where the activetectonic plates passed. One of the impact caused by earthquake is liquefaction.Liquefaction is a phenomenon where the soil loss it’s strenght due to the tremor.Liquefaction occurs in loose sandy soil (not solid) and highly contained by water. Thestudies location is located in Panjangrejo village and surrounding, Sub-district Pundong,Bantul Regency, Special Region of Yogyakarta. The studies is located in South JavaRegion, which included in earthquake prone area. In a research location included in theYoung Mount Merapi Volcaniv Deposit Formation (Qmi) which contained by loosematerial result by volcanic deposits and Nglanggran Formation (Tmn) which composedby volcanic breccia. The depth of groundwater on the studies area is relatively shallow.The purpose of this research is to determine zoning area with potential liquefaction. This studies using lithology mapping method and groundwater surface mapping bymeasuring 41 points of recidence’s well. Another method used is mechanical soil sampletest, undisturbed type in 4 points and calculation method of analytic hierarchy process fordetermining the liquefaction prone zone. The result based on mapping method isgeological map, geomorfology map, and groundwater surface map. Based on the result of data processing and the result of soil test and direct sheartest on undisturbed type of soil sample test, result obtained in the area Klisat (watercontent 25.07%, porosity 49.57%, cohession 0.06 kg/cm2), Panjang Area (water content20.82%, porosity 47.67%, cohession 0.04 kg/cm2), Nglorong Area (water content32.35%, porosity 52.54%, cohession 0.13 kg/cm2) and Ngentak Area (water content26.40%, porosity 50.24%, cohession 0.11 kg/cm2). The result of measurements ofgroundwater surface and soil mechanics test result are used as paremeter factor forcalculation using analytic hierarchy process method for making clasification from thosearea based on their class value. From the calculation results, obtained three classes ofpotential liquefaction susceptibility zonation, first is a zone of high liquefaction potential,zone of medium / moderate liquefaction potential, and low – very low liquefactionpotential.